Design Patterns with Java An Introduction - Musch, Olaf. (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2023)
A practical description of the software design patterns as they are mentioned in the 1994 book "Design Patterns - Elements of Reusable Object Oriented Software" by the author group Gamma, Helm, Johnson and Vlissides (also called "Gang of Four"). All patterns are explained in detail by means of examples and also critically appreciated. Furthermore, design principles of object-oriented programming are described and considered. All examples are commented in detail in the source code and are executable under Java 16. In some cases, newer features of Java up to and including version 16 are also explained and used. The contents - What are design patterns - How to describe them - Object-oriented design principles - All 23 original design patterns of the "Gang of Four" - Combining design patterns The target audience - Pupils, trainees and students of computer science - Programming beginners after the first steps in Java The author Olaf Musch is a computer scientist, has developed software himself for many years and now works as a project manager in the IT department of a large company in Lower Saxony. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
What are design patterns -- How to describe them -- Object-oriented design principles -- All 23 original design patterns of the "Gang of Four" -- Combining design patterns.
Keywords: Computer programming; Programming languages (Electronic computers).; Compilers (Computer programs).; Software engineering; Programming Techniques; Programming Language; Compilers and Interpreters; Software Engineering